Deterioration in glycemic control on schooldays among children and adolescents with type 1 diabetes: A continuous glucose monitoring-based study - Ding, Yu; Zhang, Wenhao; Wu, Xiumei; Wei, Tian; Wang, Xulin; Zheng, Xueying; Luo, Sihui (Frontiers in Pediatrics, 2022)
Background: To investigate the effect of school life by comparing the glycemic control between holidays and schooldays in children and adolescents with type 1 diabetes (T1D). Methods: This observational study enrolled school-aged students with T1D (aged 6 to 19) from September 2019 to July 2021. Continuous glucose monitoring (CGM) records were processed and divided into holidays and schooldays. Other information was collected via questionnaires. We compared the results using paired T-test, Wilcoxon paired test and logistic regression analysis. Results: 78 paticipants were included (40 boys, mean age 9.95 years). A total of 142,945 hours of CGM data were analyzed. Overall, TIR (3.9-7.8 mmol/L) during holidays was better than schooldays [56.97 (SD 15.03) vs. 55.87 (15.06), %, p = 0.039]. On nocturnal (0-6 am) glycemic fluctuation, TIR was longer in children aged 6-10 [60.54 (17.40) vs. 56.98 (SD 16.32), %, p = 0.012] during holiday and TAR (7.8 mmol/L) was shorter [31.54 (17.54) vs. 35.54 (16.95), %, p = 0.013], compared with schooldays. In adolescents aged 10-19 years, TAR was also significantly shorter during holidays. Stratified analysis showed that girls, patients with longer duration, and insulin pump users had more pronounced worsening of nighttime glycemia on schooldays. Logistic regression analysis showed that girls had higher risk of worse nocturnal glycemic control [3.26, 95% CI (1.17, 9.72), p = 0.027] and nocturnal hyperglycemia [OR = 2.95, 95%CI (1.08, 8.56), p = 0.039], compared to boys. Conclusions: Children and adolescents with T1D were found to have worse glycemic control in nighttime during schooldays.